A sensitive whole-cell biosensor for the simultaneous detection of a broad-spectrum of toxic heavy metal ions - Cerminati, Sebastián (2015)
Bacterial biosensors are simple, cost-effective and efficient analytical tools for detecting bioavailable heavy metals in the environment. This work presents the design, construction and calibration of a novel whole-cell fluorescent biosensory device that, simultaneously and with high sensitivity, reports the presence of toxic mercury, lead, cadmium and/or gold ions in aqueous samples. This bio-reporter can be easily applied as an immediate alerting tool for detecting the presence of harmful pollutants in drinking water.